Bells in small ruminant farming in Mediterranean pastures - Bellos G.K. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Animals’ bells have facilitated the work of livestock farmers around the Mediterranean since ancient times, both in mountain pastures and in lowland areas. The purpose of this study was to record the viewpoint of small ruminant farmers about the significance the bells have for them nowadays. The empirical study was conducted with 29 small ruminant farmers in Greece, by using the semi-structured interview technique. The results showed that bells help shepherds locate their flock or even individual animals within the flock at a considerable distance, thus saving time and cost. Bells also help them to check whether animals graze serenely or are exposed to external dangers. In normal grazing conditions, the soft tinkling of the bells neutralize external noises, thus promoting gentle grazing and enhancing the animals’ ability to locate one another. At the same time, as far as small ruminant farmers are concerned, bells could be a source of pride and social acceptance by fellow farmers. Bells also contribute to the shepherd’s enjoyment as they seek to use appropriate combinations of bells that deliver harmonious and pleasant sounds. Although nowadays there are much more modern means for locating animals and for farmers’ entertainment, bells continue to play an important role for the majority of Greek transhumance farmers.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)